Expression of Coagulation Factor IX in a Haematopoietic Cell Line - Rodriguez, M. H.; Enjolras, N.; Plantier, J. L.; Réa, M.; Leboeuf, M.; Uzan, G.; Bordet, J. C.; Négrier, C. (Thrombosis and Haemostasis, 2002)
We have developed a gene therapy project for haemophilia B which aims to express factor IX (FIX) in haematopoietic lineage. Haematopoietic stem cells and subsequent megakaryocyte-derived cells represent the target cells of this approach. Our speculation is that platelets can deliver the coagulation factor at the site of injury, and subsequently correct the haemostasis defect. In order to direct FIX expression in cells from the megakaryocytic lineage, we designed a FIX cassette where the FIX cDNA was placed under the control of the tissue-specific glycoprotein IIb (GPIIb) promoter. In stably transfected HEL cells, FIX production was higher when driven by the GPIIb promoter compared to the CMV promoter. Using a cassette containing both the GPIIb promoter and a truncated FIX intron 1, FIX synthesis was dramatically increased in HEL cells. Northern blot analysis demonstrated an increase in FIX mRNA amounts, which paralleled with an increase of FIX antigen in the culture supernatants. Using a one-stage clotting assay and an activation by FXIa and FVIIa/TF, the HEL-derived recombinant FIX was shown to be a biologically active protein. This recombinant protein exhibited a 60-kDa molecular mass and was more heterogeneous than plasma immunopurified FIX (Mononine®). The molecular mass difference could be partly explained by a different glycosylation pattern. The GPIIb promoter appears therefore to be a very attractive sequence to specifically direct FIX production in the megakaryocytic compartment of hematopoietic cells. These data also demonstrate that hematopoietic cells may represent potential target cells in an approach to gene therapy of haemophilia B.
Keywords: Factor IX; haemophilia; glycoprotein IIb promoter; haematopoietic cell line